Development and evaluation of i-ProMaths module in calculus among matriculation students - Ramli, Mohd Shahridwan; Mohd Ayub, Ahmad Fauzi; Wan Norudin, Siti Wan Aminah; Razali, Fazilah; Ghazali, Norlizah (Human Resources Management Academic Research Society (HRMARS), 2024)
The development of teaching aids in mathematics is crucial as a primary reference for students and lecturers. However, there is a notable issue where no specific mathematics modules or textbooks are provided by the Ministry of Education for matriculation students. Furthermore, previous studies have shown that students in higher education institutions, including those in matriculation, struggle with understanding calculus. Needs analysis also indicates that matriculation students face difficulties in calculus. Consequently, a study was conducted to develop a calculus module for the matriculation level. This module, named the i-ProMaths module, was developed using the ADDIE model, encompassing five main phases: analysis, design, development, implementation, and evaluation. During the evaluation phase, the i-ProMaths module was assessed by seven experts, including two Subject Matter Experts, two senior lecturers, a head of the mathematics unit, an excellent lecturer, and a curriculum officer. The module received a validity score of 0.95, which is very high. Additionally, the i-ProMaths module underwent a pilot study with 28 matriculation students. Reliability testing showed Cronbach's alpha value of 0.93, indicating high reliability. Hence, the i-ProMaths module can be considered to have high validity and reliability, making it suitable for use by matriculation students.